Perception of quality and patient satisfaction in specialized hospitals in central Peru - Padilla-Florian, Maria (2023)
Objective. Assess the relationship between user satisfaction and the quality of care in hospitals, and analyze patient perceptions across various care dimensions. Methods. Structured surveys were administered to a sample of 281 patients across multiple hospitals. Analyzed dimensions included communication, reliability, responsiveness, safety, among others. Spearman's correlation was employed to determine the relationship between user satisfaction and the quality of care. Results. Over 50% of respondents rated hospital communication and safety as "Acceptable." However, aspects like reliability and responsiveness need attention, as approximately 42.7% and 47.7% of patients, respectively, deemed them "In progress." A moderate positive correlation (r=0.344, p<0.05) between user satisfaction and the quality of care was found. Conclusions. User satisfaction is significantly associated with the perceived quality of care in hospitals. Despite the positive perception in some areas, it is imperative to address specific dimensions to ensure optimal care and enhance the patient experience.